Hubungan Kemampuan Mobilitas dengan Pressure Ulcer pada Pasien Rawat Inap - Juliana Juliana; Syarifah Rauzatul Jannah; Hilman Syarif (Journal of Telenursing (JOTING), 2023)
This study aims to determine the relationship between mobility ability and pressure ulcers in patients in the inpatient ward of the Aceh General Hospital. The method used is descriptive quantitative with a cross sectional research design. The results of the study showed that there was a relationship between mobility ability (p=0.000) and pressure ulcers in the inpatient room at Aceh General Hospital. The conclusion is that the lower the patient's level of mobility, the more severe the pressure ulcers they experience. Family participation is really needed to help patients who experience limited mobility so that they can still carry out routine repositioning. Key words: Mobilization ability; Inpatients, Pressure ulcers